Quality Evaluation of Instant Mosa (A Fried Maize Based Snack) Produced from Fermented Maize and Sorghum Flour - R.B, Abdus-Salaam; A.C, Arohunmolase; K.O, Kareem (Journal of Food Technology Research, 2021)
The study evaluated the quality of mosa produced from fermented maize and sorghum flour. The grains were subjected to fermentation, drying and milling to obtain four samples coded MFDS (Milled Fermented Dried Sorghum), MFDM (Milled Fermented Dried Maize), FDMM (Fermented Dried Milled Maize) and FDMS (Fermented Dried Milled Soghum). Proximate, functional and physiochemical analysis were determined on the flour with sensory evaluation of the fried mosa using the traditional fermented wet milled maize as control. The value of protein, fat, crude fiber, ash and carbohydrate ranged from 4.25-7.06, 0.42-0.71%, 0.27-0.46%, 2.17-3.26% and 29.85-88.72% respectively. There was no significant difference (p>0.05) between sample FDMS and FDMM in respect to protein, fat and crude fibre. Also, there was no significant difference (p>0.05) between samples FDMS and MFDM with respect to ash and carbohydrate. The water absorption capacity, oil absorption, swelling capacity and solubility ranged were 0.65-0.74 g/ml, 26.33-88.33 g/ml, 13.00-81.00 g/ml, 3.93-9.04 g/ml and 0.20-7.00% respectively. FDMS, FDMM and MFDS did not differ significantly (p>0.05) in bulk density, swelling capacity and solubility. The value of pH and TTA ranged from 4.19-6.86 and 0.05-0.34 respectively. The colour, taste, flavor, appearance, texture and overall acceptability ranged 6.27-8.10, 4.93-7.80, 4.80-7.40, 6.57-7.50, 4.87-7.47 and 5.73-7.87 respectively. The sensory scores revealed no significant difference (p>0.05) between sample FMWM, MFDM, FDMS and FDMM with respect to taste, colour, flavor and overall acceptability. The study shows that a more nutritious mosa can be produced from fermented sorghum grains, followed by drying and milling.